Integrated production, material handling scheduling in flexible manufacturing system - Ji, Zhenlin (Nanyang Technological University, 2022)
Flexible manufacturing system is a dynamic and systematic process that converts raw materials or small components into finished products according to the customers’ various requirements. In this dissertation, a novel simulation-based system for real-time FMS control is presented. The framework is based on combining the real application systems and the simulation controlled by a DES (Discrete Event System) step execution tool. Simulation is an important part of system analysis which can be used to verify the correctness of the optimized controller. For the simulation part, we use Visual Components 3D simulation software to design a 3D simulation model of a mini production line. For the control part, the Automata Debugger tool is employed to send control commands. There is also a communication hub to transmit sensor data among the controller, simulation, and the real manufacturing system via OPC-UA protocol and TCP/IP protocol, and all the communication is carried out in a parallel way. The novelty of this dissertation is that once the signal of the hardware interface is set up, the production strategy can be changed easily and applied quickly without adjusting the components in the model, and the result of the simulation has proven its effectiveness. The potential benefits of this research are quite significant in the practical application that it can be connected to the real cyber-physical system, where efficient simulation and control techniques will have a direct impact on productivity and profitability.